Diagnosis of Zoonotic Diseases in Eastern and North Eastern Region of India - Bandyopadhyay, Subhasish; Nanda, P. K.; Bandyopadhyay, Samiran; Dandapat, P. (Indian Farming, 2015)
The IVRI’s Eastern Regional Station at Kolkata has a number of achievements to its credit, related to the problem-oriented research with emphasis on zoonotic diseases. The Centre continues to carry out its various research activities in full swing.